2021
DOI: 10.1002/jgh3.12691
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between sorafenib and lenvatinib as the first‐line therapy in the sequential treatment of unresectable hepatocellular carcinoma in a real‐world setting

Abstract: Aims: There is a paucity of comparative data on the use of sorafenib and lenvatinib for unresectable hepatocellular carcinoma. We assessed the real-world treatment outcomes between using sorafenib and lenvatinib for unresectable hepatocellular carcinoma in the multiple molecular-targeted therapy era. Methods and Results: We enrolled 386 patients treated with sorafenib or lenvatinib as the first-line therapy for unresectable hepatocellular carcinoma at multiple centers. Propensity score matching was performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…The published year ranged from 2018 to 2022, and the regions studied included Asia, Europe, and North America. The dosage of the drugs was consistent in the majority of the studies ( 13 , 18 , 19 , 21 24 , 26 28 , 31 ). For instance, the initial dose of sorafenib was 400 mg twice daily, while lenvatinib was administered at a dose of 12 mg once daily for patients with body weights ≥ 60 kg or 8 mg once daily for those with body weights < 60 kg.…”
Section: Resultsmentioning
confidence: 52%
See 4 more Smart Citations
“…The published year ranged from 2018 to 2022, and the regions studied included Asia, Europe, and North America. The dosage of the drugs was consistent in the majority of the studies ( 13 , 18 , 19 , 21 24 , 26 28 , 31 ). For instance, the initial dose of sorafenib was 400 mg twice daily, while lenvatinib was administered at a dose of 12 mg once daily for patients with body weights ≥ 60 kg or 8 mg once daily for those with body weights < 60 kg.…”
Section: Resultsmentioning
confidence: 52%
“…Furthermore, the cost-utility analysis showed that lenvatinib offered similar clinical effectiveness at a lower cost than sorafenib, indicating that lenvatinib may be a cost-saving alternative in patients with advanced HCC (40). However, recent studies that compared the efficacy of lenvatinib and sorafenib in HCC found conflicting results (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)41), and hence the optimal choice for the patient between these two drugs remains controversial. Therefore, our primary aim to perform this systematic review is to evaluate the feasibility and safety of lenvatinib as a first-line treatment for advanced HCC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations